2022
DOI: 10.1111/aej.12696
|View full text |Cite
|
Sign up to set email alerts
|

Gap volume and sealer penetration of C‐shaped root canals obturated with cold hydraulic technique and calcium silicate sealer

Abstract: This study compared the gap volume and sealer penetration in C‐shaped root canals prepared with adaptive core rotary files and obturated with cold hydraulic compaction using calcium‐silicate sealer, warm vertical hybrid compaction, or lateral compaction using epoxy‐resin sealer. Thirty‐six extracted mandibular molars with pulpal floor configuration Types I and III were used. The teeth were prepared using XP‐Shaper and XP‐Finisher and obturated with: group 1: cold hydraulic compaction/calcium silicate, group 2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Samples obturated with CHC techniques showed a significantly higher void percentage among groups in the apical third. Wisawantin et al [ 17 ] reported similar findings with obturating natural C-shaped canals with bioceramic sealers and CHC technique compared with epoxy-resin sealers. They also reported spreader tracts in samples obturated with this technique.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Samples obturated with CHC techniques showed a significantly higher void percentage among groups in the apical third. Wisawantin et al [ 17 ] reported similar findings with obturating natural C-shaped canals with bioceramic sealers and CHC technique compared with epoxy-resin sealers. They also reported spreader tracts in samples obturated with this technique.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have explored various C-shaped canal obturation techniques with resin sealers using printed resin replicas [ 19 , 20 ]. However, research on obturating C-shaped canals with bioceramic sealers is scarce [ 17 ]. Given the bioceramic sealers’ favorable properties, easy application, and capability to reach anatomically challenging areas, they emerge as potential filling material in the root canal treatment of teeth with complex anatomies [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the obturation of the C-shaped root canal system, the cold hydraulic technique combined with calcium silicate sealer was chosen. This method is not only convenient but also capable of achieving a root-filling quality comparable to that of warm vertical compaction or lateral compaction with epoxy resin sealer [ 32 ]. The effectiveness of this approach was clearly demonstrated in the post-obturation radiograph, showing the successful implementation of the technique and the thorough filling of the complex canal system.…”
Section: Discussionmentioning
confidence: 99%